Attenuating Cardiac Pulsations within the Cochlea: Structure and Function of Tortuous Vessels Feeding Stria Vascularis. (19th May 2013) - Carraro, Mattia; Negandhi, Jaina; Kuthubutheen, Jafri; Propst, Evan J.; Kus, Lukas; Lin, Vincent Y. W.; Harrison, Robert V.
Abstract : The mammalian ear has an extraordinary capacity to detect very low-level acoustic signals from the environment. Sound pressures as low as a few μ Pa (−10 dB SPL) can activate cochlear hair cells. To achieve this sensitivity, biological noise has to be minimized including that generated by cardiovascular pulsation. Generally, cardiac pressure changes are transmitted to most peripheral capillary beds; however, such signals within the stria vascularis of the cochlea would be highly disruptive. Not least, it would result in a constant auditory sensation of heartbeat. We investigate special adaptations in cochlear vasculature that serve to attenuate cardiac pulse signals. We describe the structure of tortuous arterioles that feed stria vascularis as seen in corrosion casts of the cochlea. We provide a mathematical model to explain the role of this unique vascular anatomy in dampening pulsatile blood flow to the stria vascularis.